Analisis Kebutuhan Pengembangan Kompetensi Pegawai Administrasi Umum Golongan II dan III Di Kabupaten Bandung (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Civil Servants (PNS) are still often associated with negative views such as corruption, collusion, nepotism, lack of discipline, lack of competence, lengthy bureaucracy and inefficiency. Several factors are thought to have an influence on the performance of civil servants, including education and training, discussing studies on the Analysis of Technical Human Resource Development for General Administration of Civil Servants Group II and III. The aim of increasing the competency of civil servants, especially groups II and III, is that they are able to carry out their duties professionally. The method used is mix methods. The approach applied is a descriptive approach, which aims to obtain an in-depth understanding of the qualitative and quantitative aspects of competency and the population consists of 85 Class II civil servants and 91 Class III employees. So, in total, there were 176 people who were respondents in the scale distribution. The results of the study show that 1) General Administration Competencies are required by class II and III civil servants regardless of educational background; 2) Class II civil servants must have 11 aspects of competency including main tasks, teamwork and communication; 3) Class III civil servants need to have 18 aspects of competency including duties, management, technology and conflict; 4) Competency measurement is carried out through self-assessment; 5) The majority of class II civil servants are quite competent but require improvement; 6) Training needs for class II civil servants including communication, problem solving and technical; 7) Development of class III civil servants including communication, decision making and technical matters; 8) Increasing the competency of class II civil servants through strategic planning monitoring, good working relationships and awards; 9) Increasing the competency of class III civil servants through strategic planning monitoring, problem handling and conflict resolution.